A Comparison of Methods to Assess Mastectomy Flap Viability in Skin-Sparing Mastectomy and Immediate Reconstruction: A Prospective Cohort Study. Issue 2 (February 2016) - Rinker, Brian
Abstract : Background: Skin-sparing mastectomy with immediate reconstruction can yield excellent aesthetic results, but high rates of mastectomy flap necrosis have been reported. A prospective cohort study was undertaken to compare three methods of assessing mastectomy flap viability following skin-sparing mastectomy and immediate reconstruction to determine which is most effective in reducing mastectomy flap necrosis. Methods: The study group included 60 consecutive patients (99 breasts) undergoing skin-sparing mastectomy and immediate reconstruction with either tissue expanders ( n = 39) or transverse rectus abdominis musculocutaneous flaps ( n = 21). Mastectomy flap viability was assessed either visually ( n = 20), with fluorescein dye and Wood's lamp imaging ( n = 20), or by indocyanine green angiography ( n = 20). Variation across groups was analyzed using analysis of variance for continuous variables and chi-square test for dichotomous variables. Results: The mean follow-up was 10 months. There were no significant differences in mean age, body mass index, medical history, smoking history, pathologic diagnosis, chemotherapy, or reconstruction type. Mastectomy flap necrosis was observed in eight of 30 breasts in the direct visualization group (27 percent), compared with 14 percent in the indocyanine green angiography group and 3 percent in the fluorescein group ( p = 0.03). The reoperation rate in the direct visualization group was 20 percent, compared with 15 percent in the indocyanine green angiography group and 0 percent in the fluorescein group. Conclusions: Fluorescein dye was associated with the lowest rate of complications after skin-sparing mastectomy, but indocyanine green angiography was also shown to reduce mastectomy flap necrosis compared with direct visualization. Routine imaging of mastectomy flap perfusion seems to be beneficial in skin-sparing mastectomy, but intravenous fluorescein may be as effective as more expensive modalities. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.